Quantized-feedback hands-off control for nonlinear systems - Sachan A.; Xiong X.; Soni S.K.; Kamal S.; Ghosh S. (My University, 2025)
This paper addresses a quantized feedback hands-off control for a class of nonlinear systems. Here, (Formula presented.) sector is constructed with the suitable choice of control-Lyapunov function. With adjustment policy of quantization parameters, the quantized feedback hands-off control can force the states of the nonlinear feedback system to the interior of a continuous-time (Formula presented.) sector infinite time and the Lyapunov-candidate function decreases automatically inside the designed sector. Finally, the effectiveness of the proposed method is illustrated by numerical examples. © 2021 The Authors. IET Control Theory & Applications published by John Wiley & Sons Ltd on behalf of The Institution of Engineering and Technology